Constructing Islamic Preacher Personal Branding via Digital Public Relations Strategies on Instagram and TikTok: a Comparative Case Study of Gus Kautsar - untung famuji; Enung Asmaya; Gozali; Siti Nuri Nurhaidah; Ahmad (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2026)
The dissemination of Islam in Indonesia is undergoing a paradigm shift in which a preacher’s image is constructed in a decentralized manner through social media, with public relations (PR) operating not top-down from official management but through organic fan participation. This study maps and compares content strategies on Instagram and TikTok in constructing the personal branding of Gus Kautsar as an authentic, humble preacher close to Millennials and Generation Z. Employing a qualitative comparative case study design, it analyzes the 120 most popular content pieces from major fan-page accounts between January 2024 and March 2026, using thematic reduction with the eight laws of personal branding (Montoya, 2002) as the primary framework, supported by the Share/Optimize/Manage/Engage digital PR model (Luttrell, 2018) and a parasocial intimacy strategy matrix for millennial preachers. The findings reveal a complementary synergy between the two platforms that forms an audience engagement funnel: TikTok dominates the top-funnel awareness function through short, humorous clips, distinctive linguistic accents, and high virality, while Instagram assumes the mid-to-bottom funnel role, facilitating the depth of dawuh (teachings) narratives, visual aesthetics, and contemplative community interaction. Gus Kautsar’s branding is thus constructed cohesively through an organic, polycentric PR ecosystem without his official account, with message authenticity and emotional resonance as the primary catalysts mobilizing fans as active distribution agents. The study contributes to digital PR literature by demonstrating the effectiveness of organic earned media in syiar practices and offering a hybrid strategic framework for preachers and Islamic institutions navigating the algorithmic ecosystem.